Influence оf trоmbоfily genes оf the krоve cоulding system in wоmen with cоmplicatiоns оf pregnancy оf the kazakh ethnic grоup (Experimental biology, 2018)
Frequency of occurrence of polymorphic thrombophilia genes of the blood clotting system in 120 pregnant women with obstetric complications and 121 women with the physiological course of pregnancy of the Kazakh ethnic group was analyzed in this study. The frequencies of four genes were investigated: the polymorphism of the prothrombin G20210A gene, the G1691A allele variant of the fifth factor “Leiden” of the clotting system, the G10976A marker of the F7 gene, the G455A polymorphism of the FGB gene. The method of PCR analysis of thrombophilia genes in real time was applied. Amplification products were determined on the CFX96 (BiоRad, USA) automatically. Analysis of the data showed no statistically significant differences in the frequency of occurrence of alleles and genotypes of all the studied genes in both groups of pregnant women examined. A low frequency of occurrence of mutant allele A of the prothrombin gene (F2) among women at risk compared with the control is lower1.5 times, where as an increase in the frequency of the mutant allele A of the Leiden gene (F5) is 4.2 times, respectively. There is a lack of homozygous genotypes in the mutant alleles of the F2 and F5 genes (Leiden) of both groups of the examined women, which corresponds to the literature on Asian populations.
Keywords: pregnancy complications, blood coagulation system, thrombophilia, polymorphism of genes.